Three Different Abnormalities in Pulmonary Arteries in Behçet - Bouakl, Imad (2020)
A 32-year-old-man presented with a 2-year history of fatigue and weight loss. Two months before, he started having cough hemoptysis and dyspnea on minimal exertion. He also reported recurrent oral ulcers. He had no arthritis, skin rash, or ocular symptoms. CT angiogram of the chest (Figs. A and B) showed an absence of the right pulmonary artery and an aneurysmal dilatation of the left lower lobe pulmonary artery with intraluminal thrombus, causing complete occlusion of the posterior basal segmental branch (Fig. C). An echocardiogram showed well layered echodensity on the anterior surface of the RVOT with severe pulmonary valve regurgitation and mild global hypokinesia with an estimated ejection fraction of 45% to 49%. Based on the International Criteria for Behçet’s disease (ICBD), our patient was diagnosed with Behçet’s disease and immunosuppressive treatment was initiated. While both pulmonary artery aneurysms and thrombosis are classical for pulmonary involvement in Behçet’s disease, to our knowledge, complete pulmonary artery atresia has never been reported.